The composition, geographical variation and antimicrobial activity of Lippia javanica ( Verbenaceae ) leaf essential oils - Subramoney, Sivanasen (My University, 2003)
Lippia javanica is a widely spread woody shrub and the major traditional use is reflected in its vernacular name; fever tea ' koorsbossie '. An infusion of the leaves is also used as a decongestant for colds and coughs. Infusions may also be used topically to treat scabies and lice A preliminary study indicated that the essential oil chemistry varies dramatically both within and between natural plant populations.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master in Science ( Medicine ) Pharmaceutical Affairs
Keywords: Anti-Infective Agents; Lippia; Plant Leaves; Verbenaceae